PRODUKSI GAS METANA DARI PENGOLAHAN SAMPAH PERKOTAAN DENGAN SISTEM SEL - Arie Herlambang; Henky Sutanto; Kusno Wibowo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Waste to energy now become one of the technology solution that is in many developed countries, in an effort to reduce greenhouse gas emissions from waste. Urban organic waste is a potential source of greenhouse gases. Methane gas is an energy source that can be used as fuel. It is difficult to find land for Landfill alocation in the major cities and often becomes a difficult social problem. Structured Landfill Cell is used to treat the waste at the landfill, with the aim to use land more scalable, easier waste management and control, better sanitation, better water control leachate and gas produced can bemanaged optimally and compost can be utilized with the production and quality control.This new system was first used in Indonesia by PT Navigats Organics Energy Indonesia in landfill Suwung, Denpasar, Bali. There are 5 cells already built in Suwung and two of cells have been filled with garbage. Each cell contains 12,000 m3 soliswaste. Observations carried out on gas productivity of two cells that have been filled, with a dry treatment on cell 1 (dry cell) and a wet treatment in cell 2 (wet cell). The observed gas is CH4, CO2,and O2 as the main parameters, with the addition parameters are CO and H2S. The instrument used is the GA 2000 Plus. Observations of two cells made for 4 months, with the content of CH4 around 40 to 50% in the first month and gradually decreased to reach 18 to 25% in the fourth month. Carbondioxyde going up and down following condition of CH4 and its value ranges between 16 and 28%. Oxygen consentration around 2 to 14%.For keeping engine performance the consentration of methane should more than 28%and O2 content lower than 6%. Cell with watering will temporarily reduce CH4 and CO2 and O2 increase, but it is slowly rising again. Carbonmonoside values tend to increase with age garbage (10 sd 350 ppm), whereas irregular H2S values ranging 0 up to 24 ppm, allegedly associated with the low protein content in the trash. Sewage treatment system is proven to increase CH4 gas, yet still needed modifications of structure and the gas collector pipe system so that productivity can be improved.Key Words : Solidwaste, Metana, Cell System